Improving Students Group Activity In Mathematics Learning Through Cooperative Learning Community(CLC) Approach Using Peer Teaching - Novitasari, Evi Yulian; , Dr. Sumardi, M.Si (2013)
This research objective are: (1) improve students groups activity in mathematics learning through Cooperative Learning Community (CLC) approach using peer teaching, (2) improve learning outcomes/student achievement in mathematics learning through CLC approach using peer teaching so as to achieve the minimum passing grade. Subjects receiving action is student class VIID of SMPN 1 Surakarta totaling 26 students, the subject of implementing of action is researchers and helping subjects implementation are mathematics teachers and the principal. Techniques of collection data are test method and observation method as a principal method, as well as supporting method that include interviews, documentation and review. In this classroom action research, data analysis is descriptive qualitative. The results of this study showed a improving students group activity in mathematics learning. It can be seen from: (1) students learning cooperation currently before action of 50% , cycle I 76,92% and cycle II increase 100%, (2) the ability of students to understand the problem before action 57,69%, cycle I 76,92% and cycle II increase 88,46%, (3) questioning activity/expressionof the material received before action 50% , cycle I 69,23% and cycle II increase 84,62%, (4) students activities on doing task 46,15%, cycle I 65,38% and cycle II increase 88,46%, (5) the ability of students in presenting/explaining problem solving in front of class before action 30,77%, cycle I 50% and cycle II increase 76,92%. The conclusion of this study is that the application of this Cooperative Learning Community (CLC) approach using peer teaching can improve students groups activit y in mathematics learning.